KAJIAN TENTANG KASUS SENGKETA MEREK GS DENGAN MEREK GSJ BERDASARKAN HUKUM POSITIF DI INDONESIA - Heng, Richard Jemiel; Anasthasia, Trinity (Universitas Stikubank, 2024)
Trademark dispute cases often occur in Indonesia, such as what happened in the trademark dispute case between PT. Yuasa with PT. Golden Surya Jaya in Indonesia. PT. Yuasa holds the GS trademark, while PT. Golden Surya Jaya has a similar trademark, GSJ. This brand conflict has led to legal disputes in Indonesia. where unscrupulous companies such as PT Golden Surya Jaya imitate the GS brand which has a high reputation, this indicates urgency for the need for protection and enforcement of trademark rights with the issuance of Law No. 20 of 2016. This research had a purpose to analyze and study cases of trademark disputes that occur in Indonesia in cases of disputes that occur in Indonesia and how positive law in Indonesia can protect trademark rights from these cases and what are the legal consequences and responsibilities involved. must be provided by product imitation actors to companies that are harmed in order to provide solutions to problem solving in cases of brand disputes. The researching method is a normative juridical research method by examining the theoretical approaches, concepts and statutory approaches by examining the statutory regulations concerned with this research.